Efforts To Improve Learning Achievement of Islamic Religious Education And Character In High School Of 7th Grade Students In SMA LKMD Laha Ambon Through The Application of The Contextual Teaching Learning Model - n, Basirun (Global Science Education Journal, 2019)
This research is a classroom action research that aims to see whether there is an influence on the application of the CTL learning model in an effort to improve the learning achievement of PAI and character. The subjects in this study were students of class XII IPA-1, Laha Ambon High School LKMD with a total of 24 students in the 2018/2019 school year. This study uses instruments namely: (1) Teacher and student observation sheets; (2) List of students' attendance; (3) List of grades, (4) Student questionnaire sheet to determine student responses. This CAR procedure consists of 2 cycles with 2 meetings per cycle. Each cycle consists of four stages as follows: 1) planning; 2) implementing actions; 3) observation and evaluation of actions; and 4) reflection of actions. Data in this study were collected by interview and observation. This study uses a combination of qualitative data analysis techniques and quantitative data analysis techniques because some of the data obtained in the form of quantitative data. Qualitative data analysis from this research will be carried out through 3 stages, namely: Data reduction, data exposure, and inference. This research is said to be successful if students in Islamic religious education learning get a value of 70 (KKM = 70) or more with an average completeness level of 80% or more. The results of the study show that: (1) The contextual teaching learning model is very suitable for growing students' criticality in analyzing, differentiating, generalizing, and hypothesizing problems; (2) With the increase in student learning activities, student achievement shows a significant increase, namely by increasing the average value of student achievement from the first cycle of 67.1 with a level of student learning completeness of 25.0% increased to 83, 7 with the level of mastery learning students 87.5% at the end of the second cycle. The more intensive the application of the contextual teaching learning model, the more learning achievement and motivation of students increases. The more intensive in applying the contextual teaching learning model, the more the number or percentage of students experiencing mastery learning increases, if implemented consistently based on the correct cycle path.